USING FLORBETAPIR PET TO INCREASE DIAGNOSTIC CERTAINTY IN ATYPICAL DEMENTIAS. Issue 11 (14th October 2015) - Weston, PSJ; Paterson, RW; Lehmann, M; Modat, M; Bomanji, JB; Kayani, I; Dickson, J; Barnes, A; Cash, DM; Ourselin, S; Zetterberg, H; Toombs, J; et al.
Abstract : Amyloid PET or CSF can be used to determine Alzheimer pathology in vivo. Few studies have assessed the additional value of amyloid imaging where CSF results are equivocal. We recruited 20 cognitive patients (65.5+/–7.6 y) with MRI, neuropsychology, and CSF Aβ1–42 and tau measured during their diagnostic assessment. Individuals were selected to have a range of CSF results; ten had amnestic and ten non-amnestic presentations. Following the investigations, the treating neurologist gave a diagnosis (AD or non-AD). Four controls (63+/–7.0y) also had CSF examination. All subjects had Florbetapir PET imaging, reported as positive/negative. The clinicians were given the PET results and asked to review their diagnoses. Eighteen patients had positive Florbetapir scans; two patients and all controls were Florbetapir negative. Following initial investigations, thirteen patients were diagnosed with AD, and seven with non-AD pathology. Providing the Florbetapir result led to a change in diagnosis in seven patients, five of whom had atypical phenotypes. For all seven the CSF results were close to or in a "grey" area, where results overlapped for positive and negative PET scans. Even in individuals with CSF measures of Aβ1–42, and tau, Florbetapir PET imaging may have diagnostic utility, particularly in atypical cases and/or equivocal CSF results.